Mobile Phone Customer Loyalty in Thailand: A Path Analysis Case Study - Pumim, Adilak (Animo Repository, 2017)
Research was reviewed globally from mobile/cellular carriers to develop the six antecedents (customer satisfaction, perceived service quality, customer trust, corporate image, perceived value, and perceived switching costs) contributing to mobile customer loyalty in Thailand. Data were drawn from interviews with 515 Thai mobile users, who were asked about customer satisfaction, service quality perceptions, and customer loyalty. Findings suggest that perceived service quality and value have a direct positive influence on customer satisfaction: if the customer’s perception of service quality and customer satisfaction is high, it has a strong influence on customer loyalty. Additionally, if the perceived service quality is high, it has a direct impact on perceived value and customer satisfaction, in terms of price, value, terms, and reasonable carrier services. Finally, perception regarding switching costs is recognized in non-monetary terms and plays a key role in influencing customer loyalty.